Occupational Differences by Race and Ethnicity in the United States, 2007-2018 - Kusum Singh (Research in Applied Economics, 2024)
This study examines the extent and reasons for differences in occupational distributions by race and ethnicity in the U.S. labor market from 2007 to 2018. Using IPUMS data, the study found that racial differences in occupational distributions were lower than ethnic disparities in occupational distributions. Racial disparity in occupational distributions increased slightly, while the ethnic disparity in occupational distributions decreased from 2007 to 2018. In addition, racial and ethnic disparities in occupational distributions were found to be not only due to observed socio-demographic variables of workers but also due to other unexplained factors. The effect of unexplained variables had more pronounced effects on the racial differences in occupational distributions than on the ethnic differences in occupational distributions.